Cadmium induced ferroptosis and inflammation in sheep via targeting ACSL4/NF-κB axis - Ma, Zimeng; Yan, Shuo; Zhang, Huimin; Du, Ruilin; Cheng, Xinyue; Bao, Siqin; Li, Xihe; Song, Yongli (Frontiers in Veterinary Science, 2025)
IntroductionCadmium, a major environmental contaminant, induces progressive intestinal damage through bioaccumulation in vivo. Elucidating its pathogenic mechanisms is crucial for developing therapeutic interventions.MethodsThis study employed multi-omics approaches to systematically investigated cadmium-induced ileal dysfunction in Hu sheep and the intervention mechanisms of sodium octanoate.ResultsPhenotypic assessment revealed cadmium exposure caused intestinal barrier impairment and histopathological changes. Integrated transcriptomic-proteomic analysis revealed cadmium disrupted mitochondrial dysfunction via oxidative phosphorylation pathway inhibition. Leading to reactive oxygen species (ROS) overaccumulation. This ROS surge activated ferroptosis, which exacerbated inflammatory responses through NF-κB signaling. Cross-omics correlation analysis identified ferroptosis-related proteins as key regulators of the NF-κB inflammatory axis, suggesting ferroptosis modulation as a potential therapeutic strategy. Notably, sodium octanoate exhibited potent anti-inflammatory effects through specific binding to ACSL4, a critical ferroptosis regulatory protein, this interaction ameliorated oxidative stress and inflammation cascades while demonstrating therapeutic potential for cadmium-induced inflammation.DiscussionOur findings establish the ACSL4/NF-κB axis as a central mechanism in cadmium-induced pathology, highlighting sodium octanoate as a potential therapeutic intervention for pollutant-induced intestinal disorders.